BIG DATA ADOPTION: HOW WILL IT IMPACT GOVERNMENT AUDIT QUALITY? - Leonny Noviyana Sakti Pamungkas; Jaka Winarna; Y Anni Aryani (Jurnal Bisnis dan Akuntansi, 2024)
One of the problems and challenges in auditing is the large amount of data and complex problems. The existence of technology is currently a solution to simplify the audit process and improve audit quality. The problem is, not all auditors know the role of this technology. As a result, many still rely on manual methods that take a long time and are prone to errors. This research uses a System Literature Review (SLR) by collecting 61 articles and 6 international proceedings on data adoption in auditing in Scopus, Emerald, and SINTA. We also collected research articles conducted by Malakoute & Soumaya (2023) on audit quality factors as a simplification. We found that the impact factor of data adoption has some similarities to the audit quality factor in Malakoute & Soumaya (2023)) research. This finding indicates that Big Data can improve audit quality. In other words, if auditors apply Big Data in the audit process, it is likely that the audit results will be of high quality. This research provides an overview that can be used by auditors to consider data adoption in their implementation. If auditors apply Big Data in audits, the advantages of Big Data will affect audit quality in government. Keywords: Big Data adoption, SLR, Audit Quality, Audit Success